Preparation and performance of plasma/polymer composite coatings on magnesium alloy - Bakhsheshi-Rad, H. R. (Springer New York LLC, 2016)
A triplex plasma (NiCoCrAlHfYSi/Al2O3·13%TiO2)/polycaprolactone composite coating was successfully deposited on a Mg-1.2Ca alloy by a combination of atmospheric plasma spraying and dip-coating techniques. The NiCoCrAlHfYSi (MCrAlHYS) coating, as the first layer, contained a large number of voids, globular porosities, and micro-cracks with a thickness of 40-50 μm, while the Al2O3·13%TiO2 coating, as the second layer, presented a unique bimodal microstructure with a thickness of 70-80 μm. The top layer was a hydrophobic polymer, which effectively sealed the porosities of plasma layers. The results of micro-hardness and bonding strength tests showed that the plasma coating presented excellent hardness (870 HV) and good bonding strength (14.8 MPa). However, the plasma/polymer coatings interface exhibited low bonding strength (8.6 MPa). The polymer coating formed thick layer (100-110 μm) that homogeneously covered the surface of the plasma layers. Contact angle measurement showed that polymer coating over plasma layers significantly decreased surface wettability. The corrosion current density (icorr) of an uncoated sample (262.7 µA/cm2) decreased to 76.9 µA/cm2 after plasma coatings were applied. However, it was found that the icorr decreased significantly to 0.002 µA/cm2 after polymer sealing of the porous plasma layers.